The Need to Belong (NB) in Adolescence. Adaptation of a scale for its assessment - Leibovich, Nora Blanca (2018)
The need to belong (NB) is a fundamental human motive and consists of a strong impulse to form and maintain a minimum amount of meaningful and positive interpersonal relationships. The aim of this paper is to present the adaptation of the NB scale for its use with adolescent students. 709 youths between 12 and 20 years old of the City of Buenos Aires (Mean = 14.97, SD= 1.73) participated. The NB scale shows adequate reliability indicators, evidence of content validity and construct validity. The NB was studied in relation to sex and age. The obtained results show that female adolescents present a higher NB level indicating the relevance of considering gender in psychological phenomena strongly influenced by the socio-cultural context. Key Words: Need to Belong - Adolescence - Social Activities - Psychological Assessment.